Illustrated key to the genera and catalogue of Mymaridae (Hymenoptera) in the Neotropical region - Huber, John T.; Read, Jennifer D.; Triapitsyn, Serguei V. (Zootaxa, 2024)
This paper summarizes the current knowledge on Neotropical Mymaridae. Separate identification keys for females, and for males where known, are given for the 60 valid genera of Mymaridae in the Neotropical region south of Mexico but including Bermuda and the islands of the Caribbean Sea. The subgenera of four genera (Anagrus Haliday, Anaphes Haliday, Erythmelus Enock and Polynema Haliday) are also included in the key to females. The genera are illustrated with 356 photographs. The 298 valid species reported from the region are catalogued. Host genus and, sometimes, species records are reported for 15 genera and 61 species of Mymaridae from rearings undertaken in the region. The hosts identified to order and sometimes to family are known for a few additional genera. An appendix lists the 34 species from Mexico but not recorded in the Neotropical region as defined in this publication. Tanyostethium Yoshimoto, syn. n., is synonymized under Erdosiella Soyka and its type species Tanyostethium elongatum Yoshimoto is transferred to Erdosiella as Erdosiella elongatum (Yoshimoto), comb. n. †Palaeopatasson Witsack, syn. n., is synonymized under Schizophragma Ogloblin and its type species, †Palaeopatasson grollei Witsack is transferred to Schizophragma as Schizophragma †grollei (Witsack), comb. n. One new genus in the Polynema group of genera is described from the New World, Quasipalaeoneura Triapitsyn & Huber, gen. n., with the type species Polynema mymaripennis Dozier. Palaeoneura mymaripennis (Dozier) and P. durwest Triapitsyn are transferred to Quasipalaeoneura as, respectively, Quasipalaeoneura mymaripennis (Dozier), comb. n. and Quasipalaeoneura durwest (Triapitsyn), comb. n..